avaliação do metabolismo glicêmico em pacientes transplantados depâncreas com enxerto pancreático funcionante através do sistema demonitorização contínua da glicose (cgms) - Marcio Weissheimer Lauria (2010)
Background: The identification of pancreas transplant subjects who are at risk of returning to the diabetic state for graft loss or any other cause is difficult and often delayed. The available biochemical and imaging tools still lack precision for the early diagnosis of the disability of transplanted pancreas. Objectives: This study aimed to analyze different tools for monitoring glucose metabolism (traditional methods and continuous glucose monitoring system- CGMS) in patients with pancreas transplantation (PTX) [Pancreas Transplantation Alone (PTA) and Simultaneous Pancreas-Kidney Transplantation (SPK)] with functioning grafts. Methodology: There were two cross-sectional studies followed by a prospective observational study. The first study consisted in the comparative analysis of the following tests for assessment of glucose metabolism between functioning PTA and SPK patients: oral glucose tolerance test (OGTT), measurement of Cpeptide, HbA1C, insulin (INS), renal function and serum lipids. The second cross-sectional study used the CGMS, comparing the results in a subgroup of patients from each type of PTX to control groups: healthy individuals (HC) (negative control) and type 1 diabetic patients in intensive care (T1DM) (positive control). In a longitudinal study of five years, we analyzed the incidence of pancreatic graft loss, when it was sought to correlate the outcome with baseline data from the CGMS. Results: Sixty-four patients (46 SPK and 18 PTA) participated in the first study, with 39.8 ± 9.3 years old, predominantly male (60.9%) and having an average follow-up of 25.4 ± 10, 4 months after transplantation. Most patients with functioning pancreas transplant, maintained good glucose control without the use of exogenous insulin or oral antidiabetics (HbA1C = 5.9 ± 0.7%), although they were hyperinsulinemic (INS = 14.4 ± 9.1 uU / mL). No significant differences in glucose and lipid profile was found between SPK and PTA groups, although PTA patients had higher levels of tacrolimus (7.9 ± 2.7 vs 6.2 ± 2.0 ng/mL; p = 0.01) and worse renal function (creatinine = 1.8 ± 1.2 vs. 1.2 ± 0.7 mg/dL, p = 0.04). Forty subjects performed the study with CGMS: 12 with functioning SPK, 10 with functioning PTA, 10 HC and 8 T1DM. Mean concentration of interstitial glucose and variability were significantly higher in T1DM than in other groups in all parameters studied (p <0.05). Moreover, the PTA and SPK groups had higher levels of glucose compared to the HC (p <0.05). The comparison between the transplanted groups revealed a higher concentration of glucose in the PTA than in the SPK group (mean glucose-72 hours: T1DM= 141 ± 66.7 vs PTA=101.5 ± 18.6 vs SPK= 98.1± 18.8 vs HC= 93.6 ± 11.7 mg/dL, p <0.05 for all comparisons). The glycemic variability was similar among PTA, SPK and HC (13.2 ± 13.4 vs 12.8 ± 13.7 vs 11.7 ± 10.5 mg/dL respectively, p> 0.05), but was higher in the T1DM group (42 ± 39.1 mg/dL, p <0.05). During the prospective study, PTA group had higher graft loss rates. In this group, the time of transplant and the baseline CGMS mean glucose were higher in the group that returned to the diabetic state when compared to those who remained euglycemic (107.1 ± 22.3 vs 96.6 ± 16.5 mg/dL, p <0.05). A mean glucose level in the CGMS higher than 102 mg/dL had the greatest accuracy in discriminating between these two groups. Conclusion: This study depicts a potential usefulness of the CGMS as a tool to assess post-pancreas transplant patients in detecting subtle glycemic changes, which may have clinical significance in the long-term follow-up.